Efficacy of concurrent treatments in idiopathic pulmonary fibrosis patients with a rapid progression of respiratory failure: an analysis of a national administrative database in Japan. Issue 1 (December 2016) - Oda, Keishi; Yatera, Kazuhiro; Fujino, Yoshihisa; Ishimoto, Hiroshi; Nakao, Hiroyuki; Hanaka, Tetsuya; Ogoshi, Takaaki; Kido, Takashi; Fushimi, Kiyohide; Matsuda, Shinya; Mukae, Hiroshi
Abstract Background Some IPF patients show a rapid progression of respiratory failure. Most patients are treated with high-dose corticosteroids. However, no large clinical studies have investigated the prognosis or efficacy of combined treatments including high-dose corticosteroids in IPF patients with a rapid progression of respiratory failure. Methods We enrolled IPF patients who received mechanical ventilation and high-dose corticosteroids between April 2010 and March 2013. Records were extracted from a Japanese nationwide inpatient database. We conducted a retrospective epidemiologic and prognostic analysis. Results Two hundred nine patients receiving an average of 12.8 days of ventilatory support were enrolled. There were 138 (66 %) fatal cases; the median survival was 21 days. The short-term (within 30 days) and long-term (within 90 days) survival rates were 44.6 and 24.6 %, respectively. The average monthly admission rate among the IPF patients with the rapid progression of respiratory failure in the winter was significantly higher than that in spring (p  = 0.018). Survival did not differ to a statistically significant extent in the different geographic areas of Japan. Survivors were significantly younger (p  = 0.002) with higher rates of mild dyspnea on admission (p  = 0.012), they more frequently underwent bronchoscopy (p  < 0.001), and received anticoagulants (p  = 0.027), co-trimoxazole (p  < 0.001) and macrolide (p  = 0.02) more frequently than non-survivors. A multivariate logistic analysis demonstrated that two factors were significantly associated with a poor prognosis: >80 years of age (OR = 2.94, 95 % Cl 1.044–8.303;p  = 0.041) and the intravenous administration of high-dose cyclophosphamide (OR = 3.17, 95 % Cl 1.101–9.148;p  = 0.033). Undergoing bronchoscopy during intubation (OR = 0.25, 95 % Cl 0.079–0.798;p  = 0.019) and the administration of co-trimoxazole (OR = 0.28, 95 % Cl 0.132–0.607;p  = 0.001) and macrolides (OR = 0.37, 95 % Cl 0.155–0.867;p  = 0.033) were significantly associated with a good prognosis. The dosage of co-trimoxazole significantly correlated with survival. Conclusions Co-trimoxazole and macrolides may be a good addition to high-dose corticosteroids in the treatment of IPF patients with a rapid progression of respiratory failure.